Reliability of transcranial magnetic stimulation and H-reflex measurement during balance perturbation tasks - Hu, Nijia; Avela, Janne; Kidgell, Dawson J.; Nevanperä, Samuli; Walker, Simon; Piirainen, Jarmo M. (Frontiers in Physiology, 2022)
Following ankle movement, posterior balance perturbation evokes short- (SLR ~ 30-50 ms), medium- (MLR ~ 50-60 ms), and long-latency responses (LLR ~ 70-90 ms) in soleus muscle before voluntary muscle contraction. Transcranial magnetic stimulation (TMS) and Hoffmann-reflex (H-reflex) measurements can provide insight into the contributions of corticospinal and spinal mechanisms to each response. Motor evoked potential (MEP) and H-reflex responses have shown good reliability in some dynamic muscle contraction tasks. However, it is still unclear how reliable these methods are in dynamic balance perturbation and corticospinal modulation during long amplitude balance perturbation tasks. 14 subjects completed two test sessions in this study to evaluate the reliability of MEPs, H-reflex, and corticospinal modulation during balance perturbation. In each session, the balance perturbation system operated at 0.25 m/s, accelerating at 2.5 m/s2 over 0.3 m displacement. MEPs and H-reflexes were elicited in the right leg soleus muscle at four delays after ankle movement (10 ms, 40 ms, 80 ms, and 140 ms), respectively. Test-retest reliability of MEP and H-reflex amplitudes were assessed via intraclass correlation coefficients (ICC) both between- and within-session. Between-session test-retest reliability for MEPs was excellent (ICC = 0.928 - 0.947), while H-reflex demonstrated moderate-to-good reliability (ICC = 0.626 - 0.887). Within-session reliability for both MEPs and H-reflex was excellent (ICC = 0.927 - 0.983). TMS and H-reflex measurements were reliable at different delays after perturbation between- and within-sessions, which indicated that these methods can be used to measure corticospinal excitability during balance perturbation.